Comparing early and delayed repair of common bile duct injury to identify clinical drivers of outcome and morbidity. Issue 9 (September 2016) - Kirks, Russell C.; Barnes, T.E.; Lorimer, Patrick D.; Cochran, Allyson; Siddiqui, Imran; Martinie, John B.; Baker, Erin H.; Iannitti, David A.; Vrochides, Dionisios
Abstract: Background: Outcomes following repair of common bile duct injury (CBDI) are influenced by center and surgeon experience. Determinants of morbidity related to timing of repair are not fully described in this population. Methods: Patients with CBDI managed surgically at a single center from January 2008 to June 2015 were retrospectively reviewed. Outcomes of patients undergoing early (≤48 h from injury) and delayed (>48 h) repair were compared. Predictive modeling for readmission was performed for patients undergoing delayed repair. Results: In total, 61 patients underwent surgical biliary reconstruction. Between the early and delayed repair groups, no differences were found in patient demographics, injury classification subtype, vasculobiliary injury (VBI) incidence, hospital length of stay, 30-day readmission rate, or 90-day mortality rate. Patients undergoing delayed repair exhibited increased chance of readmission if VBI was present or if multiple endoscopic procedures were performed prior to repair. A predictive model was constructed with these variables (ROC 0.681). Conclusion: When managed by a tertiary hepatopancreatobiliary center, equivalent outcomes can be realized for patients undergoing early and delayed repair of CBDI. Establishment of evidence-based consensus guidelines for evaluation and treatment of CBDI may allow identification of factors that drive morbidity and predict clinical outcomes in this population.